Perception of sexual harassment at the workplace / Marfinny Mohamad and Azianna Alwi - Mohamad, Marfinny; Alwi, Azianna (2009)
Sexual harassment today becomes more serious. During the previous year, it is known by the society that only woman is being sexually harassed. However, nowadays in this modern world, the victim of sexual harassment is also among the man. In this research, the researchers were focusing on the sexual harassment at the workplace. The relationship of man and woman at the workplace can be beyond the rule. There are several reasons why the victims are refused to make a report to the superior. The common reason is that they are afraid of losing their job if they bring up the matter to the top level management. Other than that, the management might not easily believe on what they said and it will affect their reputation as a worker. Moreover, the victims feel ashamed of themselves because they are being sexually harassed. Men are less reported as victim of sexual harassment at the workplace because they are masculine. From the men’s point of view, reporting the matter will lead others to misjudge them as it will give bad impression to others as well. Besides, they may be afraid that others might questioned about their sexual orientation assuming that the man is homosexual or have a bit ‘different’ taste. Injury from the sexual harassment at the workplace is often extreme, including humiliation, loss of dignity, psychological injury, and can decrease the performance their career. Sometimes, they face a choice between their jobs and their own safety.